308 PROGNOSTIC FACTORS OF PATIENTS WITH LYMPH NODE RECURRENCE AFTER ESOHAGECTOMY. (17th September 2021) - Tanaka, Koji
Abstract:  : Background: Lymph node recurrence (LNrec) is a frequent form of recurrence in esophageal squamous cell carcinoma (ESCC), but is often characterized as a systemic disease. However, loco-regional treatment may provide cure for lymph node-only recurrence without distant metastases. There is no consensus on the outcome of multidisciplinary treatment, including surgical resection. The aim of this study is to identify the prognostic factors and to establish treatment strategy for LNrec. Methods: Methods: Among 1160 patients who underwent esophagectomy for ESCC between 2004 and 2017 in our hospital, 117 patients (12.4%) who had LN-only recurrence without distant recurrence were analyzed retrospectively. The standard operation consisted of subtotal esophagectomy with 2- or 3-field lymph node dissection via right thoracotomy or video assisted thoracic surgery (VATS) and gastric tube reconstruction. Recurrence site, treatment for LN rec, and survival after recurrence were examined. Survival curves were plotted using the Kaplan–Meier method, and differences between survival curves were compared using the log-rank Test. Results: The 3-year survival rate after recurrence of all lymph node-only cases was 19.5%. The 3-year survival rate after recurrence was significantly better in patients with single recurrence: 25.1%/multiple recurrence 12.4% (p = 0.0222). The 3-year survival rate after recurrence was initial p-stage: II or lower/III or higher = 39.0/14.1% (p = 0.0107). Patients with a high p-stage at initial surgery had a significantly poor prognosis. Patients who underwent local treatment (C RT or surgery) after recurrence had significantly better prognosis than those who did not (25.8/10.6%; p = 0.0006). Conclusion: Single LN rec, low initial p-stage, local treatment (CRT or surgery) were identified as prognostic factors in patients with LN-only recurrence.